The Configuration Of Supply Chain Agritourism To Improve The Performance With Dynamic Programming - Sahnaz Ubud (Department of Management, Faculty of Economics and Business, Brawijaya University, 2015)
The purposes of this research is to implementation about the configuration of Supply Chain Agritourism in Mekarsari Tours Garden and result a decision making which must be done by top level management about their supply chain configuration. Because now Mekarsari, the biggest fruit garden in the world, have a lot of type of fruit which must be supply for the customer depend on the season with on time. So Mekarsari must know about their configuration from supplier to customer to improve their performance. The Respondents for this research is selected based on the results of supply chain maping from the worker in the garden, the top level management until the end customer. Supply chian network is formed consisting of farm workers to the end customers, especially those located in the tourist are of green land zone. The type of data is displayed in a supply chain modeling approach is to use the dynamic system. It’s consists of numeric data, the written data and mental models. That data is collected and processed into a design model. The design model is using system dynamics methodology. In compiling the system dynamics model has been used software Vensim Professional Academic Ventana 5.7. The result of this research is a configuration of Supply Chain Agritourism which is developed from the supplier until the end customer in Mekarsari tours Garden. From the Dynamic Programming, the result is a decision making which must be done by the top level management to improve the supply chain performance, especially in the green land zone.